Analysis of factors influencing public employees' work cognition under a public health crisis: A survey of China's response to COVID-19 - Yang, Anhua; Zhou, Xue; Sohail, Muhammad Tayyab; Rizwanullah, Muhammad; Dai, Bo (Frontiers in Public Health, 2022)
The work cognition of public employees lays an importance in tackling an escalating health crisis situation. Among micro level and macro level, different factors contribute to different degrees of public employees’ work cognition. However there are limited studies examining the work cognition of public employees and it’s influencing factors, particularly in situations such as a public health crisis. Our research takes China's response to COVID-19 as an example. The data has been taken from the six Chinese provinces of Hunan, Hubei, Jiangsu, Shanxi, Henan and Shandong, through a total of 738 questionnaires and telephonic interviews. Furthermore, study used a Logistic Multiple Regression model to analyze the factors that influenced the public employees’ work cognition when working under a public health crisis. As result, our study found that at a micro level, the educational background, attitudes and actions (initiative, responsibility, administrative capacity, timeliness of feedback) and their level of concern with work influenced the work cognition of public employees. At a macro level, we found that it was the anti-epidemic measures that most influenced public employees’ work cognition. Our findings provide important policy implication for emergency preparedness and handling of major emergencies, and have important reference value for the management of public employees and the improvement of national governance capabilities under similar major challenges in the future.